DISEÑO DE POLÍTICA PÚBLICA PARA LA ESTRATIFICACIÓN SOCIAL A PARTIR DE LOS INGRESOS EN COLOMBIA Y ARGENTINA (2016)
This paper presents the approaches and different positions from philosophy and sociological theory drink together he debate on inequality and social stratification from a revenue perspective, which has been applied from an economic dimension to budgeting approach, hence the purpose of the theoretical research monograph is sustain a comparative analysis of public policies in Latin America apply mainly in the countries of Colombia and Argentina in terms of stratification refers.